HYDROCARBON POTENTIAL OF THE DEVONIAN SEDIMENTS OF CHERNIHIVSKO-BRAHYNSKOHO PERSPECTIVE DISTRICT - Bagriy І.; Starodubets К.; Malyshev О.; Glon, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
As a result of the analysis of wells that revealed Devonian sediments, lithostratigraphic complexes were described and the geological structure and oil and gas potential of Chernihivsko-Bragynskogo perspective district of the Eastern oil and gas region of Ukraine were compared with the Pripyat depression of the Republic of Belarus.The list of wells which gave non-industrial inflows of hydrocarbons at test is made and their main characteristics at test are described.Hrybovorudniansko-Sednivska and Olishevsko-Losynivska fields are considered from the point of view of potential prospects for hydrocarbons from compacted carbonate reservoirs of Devonian deposits. Stock data related to the results of drilling and testing of wells No655 and No217 Hrybovo-Rudnyanska square, which confirm the prospects of Hrybovorudniansko-Sednivska area, were analyzed.The issue of realization of the Chernihivsko-Bragynskyi perspective district as a site for signing a production sharing agreement is considered.The geological, methodological and technological reasons of the negative results of oil and gas exploration works in the Devonian deposits of the Chernihivsko-Bragynskyi perspective district are analyzed.